The impact of using authentic materials to promote listening comprehension in 4th grade students - Zárate Reyes, Carlos Andrés (Corporación Universitaria Minuto de Dios, 2017)
These days, globalization is opening the doors from the frontiers of communication among cultures, as now people can travel easily and the opportunities of having contact with a foreigner are higher than it used to be in the past years. This study included the participation of 34 4th graders from Prado Veraniego School where half of the course was selected randomly to get the information about their listening comprehension, afterwards a pre-test (Cambridge English: Starters (YLE starters), listening section) was placed to gather data about their listening comprehension before the implementation of authentic listening activities. Authentic videos selected taking into account students’ ages and were played to practice students’ listening comprehension within the usage of TBL (Task-Based Learning) in order to include the task cycle (1 pre-task, 2 while task and 3 post-task) where students could 1 know about the context, 2 practice listening comprehension with the audio input and 3 develop an activity related to the context. To gather the information and analyse the possible impact of implementing authentic TBL listening activities in 4th graders’ listening comprehension, three instruments were used: Teacher’s journal, Questionnaires and Classroom documents. After the sessions, the same test was placed to compare the results between the pre-test and the post-test. By analysing the results, it was evident that the authentic materials helped students’ listening comprehension as they had a good performance during the sessions because they learnt about a real context by learning vocabulary of the context, watching an authentic video and performing a post-task related to the topic but also the analysis shown that most of the participants had an improvement in the exit test. Key words: Authentic Materials, Listening comprehension, TBL (Task-Based Learning)
Analyse the possible impact of implementing authentic TBL listening activities in 4th graders’ listening comprehension
Keywords: Authentic Materials; Listening comprehension; TBL (Task-Based Learning); Listening comprehension; Educación del oído; Dictado musical; Materiales audiovisuales; Medios de enseñanza